2022
DOI: 10.3390/su142416995
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Ecological Risks Based on the Three-Dimensional Ecological Footprint Model in Gansu Province

Abstract: It has become a hot topic in sustainable development to determine how to use data series to predict the trajectory of ecological footprints (EFs), precisely map biocapacity (BC), and effectively analyze regional sustainability. The sustainability of the ecological system in Gansu province must be investigated because the province is situated in western China and serves as a significant economic and transportation hub. We used the EF model to compute the per capita EF and BC of Gansu province from 2010 to 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…We discovered that the percentage of the building land among the six land types is an important indicator of the influence on the footprint, and, in 2020, for example, the share of the building land in the eef reached 49%, much greater than the other five land types. This also represented Gansu Province's rapid economic development over the previous 20 years, the quickening process of industrialization and modernization, and the necessity to adapt the industrial structure in a timely way at the appropriate time as shown by research [39].…”
Section: Analysis Of Results and Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…We discovered that the percentage of the building land among the six land types is an important indicator of the influence on the footprint, and, in 2020, for example, the share of the building land in the eef reached 49%, much greater than the other five land types. This also represented Gansu Province's rapid economic development over the previous 20 years, the quickening process of industrialization and modernization, and the necessity to adapt the industrial structure in a timely way at the appropriate time as shown by research [39].…”
Section: Analysis Of Results and Comparisonmentioning
confidence: 99%
“…Gansu Province is a vast area with complex and diverse landscapes. The terrain is elongated, and it is 1659 km long from east to west and 530 km broad from north to south, occupying 4.72% of the total area of China [39]. Most altitudes are above 1000 m, with the most prominent mountain ranges including the Qilian Mountains and the Liupan Mountains.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Gansu is the seventh largest province in China. However, with the rapid development of our society, the natural resources of Gansu are seriously contaminated due to human activities [13].To investigate the sustainable development tourism industry in Gansu Province, this study calculated the tourism carbon footprint and tourism carbon capacity of Gansu Province in 2019 and 2020. Corresponding results may provide available measures and recommendations for balance the ecological environment and the development of tourism industry.…”
Section: Introductionmentioning
confidence: 99%